2014
DOI: 10.1111/aji.12326
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms in the Female Genital Tract during Pregnancy: Tolerance versus Pathogenesis

Abstract: Microorganisms in the pregnant female genital tract are not always associated with pathology. The factors that influence the maternal response to microorganisms remain ill defined. We review the state of knowledge of microbe-host interactions in gestational tissues and highlight mechanisms that promote tolerance or pathogenesis. Tolerance to microorganisms is promoted during pregnancy by several mechanisms including upregulation of anti-inflammatory mediators, induction of endotoxin tolerance, and possibly by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…This supports reports that G. vaginalis is not uniquely related to BV or delivery outcome ( Fredricks et al, 2005 ; Fredricks et al, 2007 ; Hillier et al, 1995 ; Vitali et al, 2015 ), being found in nearly all healthy women ( Zozaya-Hinchliffe et al, 2010 ). Taken together, our observations lend credence to a possible association between female genital tract colonisation by anaerobic bacteria, and infection/inflammation-associated sPTB ( Ramos et al, 2015 ; Romero et al, 2007 ; Taylor et al, 2013 ; Witkin et al, 2011 ). Though M. hominis, a member of the class Mollicutes, did not differ in relation to delivery outcome in this study, another member of the same class not investigated in the current study —Ureaplasma— appears implicated in intra-amniotic infection and PTB, along with M. hominis ( Keelan et al, 2016 ; Oh et al, 2017 ), and warrants further study.…”
Section: Discussionsupporting
confidence: 74%
“…This supports reports that G. vaginalis is not uniquely related to BV or delivery outcome ( Fredricks et al, 2005 ; Fredricks et al, 2007 ; Hillier et al, 1995 ; Vitali et al, 2015 ), being found in nearly all healthy women ( Zozaya-Hinchliffe et al, 2010 ). Taken together, our observations lend credence to a possible association between female genital tract colonisation by anaerobic bacteria, and infection/inflammation-associated sPTB ( Ramos et al, 2015 ; Romero et al, 2007 ; Taylor et al, 2013 ; Witkin et al, 2011 ). Though M. hominis, a member of the class Mollicutes, did not differ in relation to delivery outcome in this study, another member of the same class not investigated in the current study —Ureaplasma— appears implicated in intra-amniotic infection and PTB, along with M. hominis ( Keelan et al, 2016 ; Oh et al, 2017 ), and warrants further study.…”
Section: Discussionsupporting
confidence: 74%
“…Tolerance is a mechanism that negates or minimises the consequences of invasion by a pathogen but without the induction of inflammation. Tolerance mechanisms have been shown to be up‐regulated during pregnancy . This is undoubtedly necessary due to the negative effects of inflammation on proper fetal development as well as the triggering of premature parturition.…”
Section: Tolerance and Resistancementioning
confidence: 99%
“…Depending on the interaction between the host and microorganisms, the presence of bacteria in the maternal‐fetal unit can have beneficial or adverse effects on pregnancy and/or the fetal development. The immune tolerance that occurs during pregnancy might explain the absence of an inflammatory response to the microorganisms present in the placenta and amniotic fluid …”
Section: Microbiome and The Placentamentioning
confidence: 99%